Clinical Study of 30 Novel KCNQ2 Variants/Deletions in KCNQ2-Related Disorders - Xiao, Tiantian; Chen, Xiang; Xu, Yan; Chen, Huiyao; Dong, Xinran; Yang, Lin; Wu, Bingbing; Chen, Liping; Li, Long; Zhuang, Deyi; Chen, Dongmei; Zhou, Yuanfeng; et al. (Frontiers in Molecular Neuroscience, 2022)
Abstract Background The KCNQ2-related disorder is typically characterized as neonatal onset seizure and epileptic encephalopathy. The relationship of its phenotype and genotype is still elusive. This study aims to provide clinical features, management, and prognosis of patients with novel candidate variants of KCNQ2 gene. Methods We enrolled patients with novel variants in KCNQ2 gene from China Neonatal Genomes Project between January 2018 to January 2021. All patients underwent next generation sequencing tests and genetic data were analyzed by an in-house pipeline. The pathogenicity of variants was classified according to the guideline of American College of Medical Genetics. Each case was evaluated by two geneticists back-to-back. Patients’ information was acquired from clinical records. Results A total of 30 unrelated patients with novel variants in KCNQ2 gene were identified, including 19 patients with single nucleotide variations (SNVs) and 11 patients with copy number variants (CNVs). For the 19 SNVs, 12 missense variants and 7 truncating variants were identified. Of them, 36.8% (7/19) of the KCNQ2 variants were located in C-terminal regions, 15.7% (3/19) in segment S2, and 15.7% (3/19) in segment S4. Among them, 18 of 19 patients experienced seizures in the early neonatal period. However, one patient presented neurological development delay (NDD) as initial phenotype at his 2-month-old, and he had severe NDD at his 3-years-old. This patient did not present seizure but had abnormal electrographic background activity and brain imaging. Moreover, for the 11 patients with CNVs, 20q13.3 deletions involving EEF1A2, KCNQ2, CHRNA4 genes were detected. All of them presented neonatal-onset seizures, responded to antiepileptic drugs and had normal neurological development. Conclusion In this study, patients with novel KCNQ2 variants have variable phenotypes, while patients with 20q13.3 deletion involving EEF1A2, KCNQ2, CHRNA4 genes tend to have normal neurological development.